STRATEGI PENERAPAN LKPD DIGITAL DI SEKOLAH(INOVASI DALAM PEMBELAJARAN ABAD 21) - Wahidin Wahidin (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This study aims to explore the strategies for implementing Digital Student Worksheets (LKPD) in schools and analyze their impact on learning effectiveness. The research focuses on the application of digital LKPD, the challenges in its implementation, and the innovations generated in the context of 21st-century learning. This study employs a qualitative approach using a case study method at four junior high schools in Kuala Kapuas. Data were collected through in-depth interviews, observations, and document analysis. The subject of this research is the Strategy for Implementing Digital LKPD in Schools, an innovation in learning that emphasizes key strategies and important steps in the implementation of LKPD, as well as innovations in teaching. The research was conducted at four public junior high schools (SMPN) in Kuala Kapuas to gain a broader perspective. The informants in this study included four school principals, ten teachers, eight students, and four educational staff members. Data were collected through in-depth interviews with teachers and students, direct classroom observations, and document analysis related to the implementation of digital LKPD. The results of the study reveal that the implementation of digital LKPD in these schools has a significant positive impact, such as increasing student engagement and motivation. Digital LKPD has been shown to improve students' understanding of the material and their technological skills. The use of interactive multimedia in digital LKPD, such as Kahoot and Nearpod, has enhanced students' enthusiasm and participation in the learning process. However, this study also identified several challenges, including issues with unstable internet access and limited devices. The findings indicate that although digital LKPD offers many advantages, its success heavily depends on the readiness of infrastructure and the digital literacy of both teachers and students. Recommendations include enhancing teacher capacity through advanced training, providing adequate technological infrastructure, and developing hybrid learning solutions that combine digital and non-digital methods. This study concludes that digital LKPD has great potential to improve learning effectiveness, but its implementation requires adequate support to overcome existing challenges.